Asymmetric Cyclopropanation Reactions - Bartoli, Giuseppe; Bencivenni, Giorgio; Dalpozzo, Renato (Synthesis, 2014)
Both physical and organic chemists are interested in the cyclopropane ring, the former owing to the strain inherent to the small ring structure, the latter prompted by the importance of this ring in naturally occurring compounds. In recent years, the increasing interest in enantioselective organic synthesis has led to a large number of papers on the preparation of cyclopropane compounds in enantioenriched form. The last review on asymmetric cyclopropanation reactions is dated 2008, thus an update is necessary with critical comparison of preparations using chiral auxiliaries, chiral metal complexes and organocatalysts. The aim of this review is an overview of these topics from 2008 to mid-2013.1 Introduction2 Simmons–Smith Cyclopropanation2.1 Chiral Auxiliaries 2.2 Chiral Catalysts3 Transition-Metal-Catalyzed Decomposition of Diazoalkanes3.1 Cobalt3.2 Copper3.3 Rhodium3.4 Ruthenium3.5 Other Metals4 Michael-Initiated Ring Closure (MIRC)4.1 Chiral Auxiliaries4.2 Organocatalysis4.3 Metal Catalysis5 Miscellaneous5.1 C–H Insertion5.2 Nucleophilic Ring Closure5.3 Cycloisomerization of 1,n-Enynes5.4 Other Methods6 Conclusion7 Abbreviations
Keywords: cyclization; asymmetric synthesis; metal catalysis; enantioselectivity; carbenoids